Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/ffgc.2019.00038
|View full text |Cite
|
Sign up to set email alerts
|

Human Appropriated Net Primary Productivity of Complex Mosaic Landscapes

Abstract: Quantifying human impact on the environment is increasingly important and particularly so in complex mosaic landscapes. Such landscapes are prolific in the developing world, notably in West African, small holder cocoa farming communities. Human Appropriated Net Primary Productivity (HANPP) is a metric which has been developed to quantify the human impact on the environment and has been used in a number of studies globally. However, most operationalization's of HANPP have been done on a coarse global scale or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…its effects on vegetation types or via physiological effects influencing the identity of the extant species available for colonization within regional pools). The observed trophic-structure-NPP patterns are consistent with the idea that average scores of NPP present in any location act as a surrogate for the amount of resources available for consumption by resident animal communities (Phillips et al 2008, Pellissier et al 2018, including humans (Krausmann et al 2013, Moore et al 2019, whereas excesses scores of NPP over the mean would represent resources becoming available for harvest by external migrant species (Thorup et al 2017), a pattern apparently reproduced across geological period (Thorup et al 2021).…”
Section: Discussionsupporting
confidence: 75%
“…its effects on vegetation types or via physiological effects influencing the identity of the extant species available for colonization within regional pools). The observed trophic-structure-NPP patterns are consistent with the idea that average scores of NPP present in any location act as a surrogate for the amount of resources available for consumption by resident animal communities (Phillips et al 2008, Pellissier et al 2018, including humans (Krausmann et al 2013, Moore et al 2019, whereas excesses scores of NPP over the mean would represent resources becoming available for harvest by external migrant species (Thorup et al 2017), a pattern apparently reproduced across geological period (Thorup et al 2021).…”
Section: Discussionsupporting
confidence: 75%
“…However, even though our average HANPP values were consistent with this estimate, we also found high variability in measured HANPP across our farms and, therefore, when considering the relative representation of each land cover, average landscape values may differ. Using HANPP estimates from spatial datasets derived from drone imagery, we found values closer to 6.0 Mg C ha −1 year −1 across our study landscape, which included fallow lands and subsistence crop production (Moore et al., in review). Assuming similar dynamics across other heterogenous landscapes dominated by smallholder agriculture, we suggest caution in relying on globally derived estimates of HANPP.…”
Section: Discussionmentioning
confidence: 51%
“…At the landscape scale, studies have shown that HANPP TOT tends to increase with development and affluence, with wealthier households appropriating larger proportions of NPP (Haberl et al., ; Pritchard et al., ), a phenomenon we did not explore for this study. However, as stated, our results suggest this fixation on “efficiency” may not be as meaningful in more heterogenous, smallholder‐dominated landscapes, which current satellite remote sensing methods do not discern particularly well (Curtis, Slay, Harris, Tyukavina, & Hansen, ; Ordway et al., ) and that will require higher resolution imagery and improved classification algorithms to adequately capture (Moore, Kruitwagen, Ramirez Mendiola, Morel, & Malhi, in preparation). If we contrast these studies with results reported for industrialized countries, which have shown decreasing trends in HANPP and a supposed disconnection of HANPP with population growth and GDP (Haberl et al., ), it seems that HANPP is more a metric of the dependence of a society on natural systems, particularly agricultural, rather than being related to the level of a society's consumption.…”
Section: Discussionmentioning
confidence: 60%
“…However, this faces several issues. Tree canopies and the fine spatial scales of smallholder cocoa farming make it extremely difficult to differentiate from forest using remote sensing techniques (Moore et al, 2019;Ordway et al, 2017). As traders often buy cocoa beans already collected from varied sources, identifying producers and corresponding farms can be unfeasible.…”
Section: Sovereign Environmentality Supplanting Voluntary Behavioural...mentioning
confidence: 99%